A Multicenter Network Assessment of Three Inflammation Phenotypes in Pediatric Sepsis-Induced Multiple Organ Failure. Issue 12 (December 2019) - Carcillo, Joseph A.; Berg, Robert A.; Wessel, David; Pollack, Murray; Meert, Kathleen; Hall, Mark; Newth, Christopher; Lin, John C.; Doctor, Allan; Shanley, Tom; Cornell, Tim; Harrison, Rick E.; et al.
Abstract : Objectives: Ongoing adult sepsis clinical trials are assessing therapies that target three inflammation phenotypes including 1) immunoparalysis associated, 2) thrombotic microangiopathy driven thrombocytopenia associated, and 3) sequential liver failure associated multiple organ failure. These three phenotypes have not been assessed in the pediatric multicenter setting. We tested the hypothesis that these phenotypes are associated with increased macrophage activation syndrome and mortality in pediatric sepsis. Design: Prospective severe sepsis cohort study comparing children with multiple organ failure and any of these phenotypes to children with multiple organ failure without these phenotypes and children with single organ failure. Setting: Nine PICUs in the Eunice Kennedy Shriver National Institutes of Child Health and Human Development Collaborative Pediatric Critical Care Research Network. Patients: Children with severe sepsis and indwelling arterial or central venous catheters. Interventions: Clinical data collection and twice weekly blood sampling until PICU day 28 or discharge. Measurements and Main Results: Of 401 severe sepsis cases enrolled, 112 (28%) developed single organ failure (0% macrophage activation syndrome 0/112; < 1% mortality 1/112), whereas 289 (72%) developed multiple organ failure (9% macrophage activation syndrome 24/289; 15% mortality 43/289). Overall mortality was higher in children with multiple organ and the phenotypes (24/101 vs 20/300; relative risk, 3.56; 95% CI, 2.06–6.17). Compared to the 188 multiple organ failure patients without these inflammation phenotypes, the 101 multiple organ failure patients with these phenotypes had both increased macrophage activation syndrome (19% vs 3%; relative risk, 7.07; 95% CI, 2.72–18.38) and mortality (24% vs 10%; relative risk, 2.35; 95% CI, 1.35–4.08). Conclusions: These three inflammation phenotypes were associated with increased macrophage activation syndrome and mortality in pediatric sepsis-induced multiple organ failure. This study provides an impetus and essential baseline data for planning multicenter clinical trials targeting these inflammation phenotypes in children. Abstract : Supplemental Digital Content is available in the text.